The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/liv.13858
|View full text |Cite
|
Sign up to set email alerts
|

Shorter hepatitis B immunoglobulin administration is not associated to hepatitis B virus recurrence when receiving combined prophylaxis after liver transplantation

Abstract: Liver transplantation is an effective treatment for hepatitis B virus-related liver disease. Since the introduction of combined prophylaxis the rate of hepatitis B virus recurrence is very low. However, lifelong hepatitis B immunoglobulin administration does not seem necessary to reduce hepatitis B virus recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
2
9
1
2
Order By: Relevance
“…Twenty‐seven of 33 HCC patients with HBV recurrence also had HCC recurrence or metastasis. We found that HCC recurrence after LT was also significantly associated with HBV recurrence (HR 7.58, 95% CI 4.15‐13.84, P < .001), supporting the notion that increased virus production in recurrent HCC acts as a reservoir for HBV recurrence . Recurrent HCC after LT should be monitored closely because such patients have a relatively high risk of HBV recurrence.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Twenty‐seven of 33 HCC patients with HBV recurrence also had HCC recurrence or metastasis. We found that HCC recurrence after LT was also significantly associated with HBV recurrence (HR 7.58, 95% CI 4.15‐13.84, P < .001), supporting the notion that increased virus production in recurrent HCC acts as a reservoir for HBV recurrence . Recurrent HCC after LT should be monitored closely because such patients have a relatively high risk of HBV recurrence.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, there were no significant differences among the various antiviral agents. Second, because there were only two patients co‐infected with HCV and had no HBV recurrence during the follow‐up, the effect of co‐infection on HBV recurrence could not be analysed, even though co‐infections have been reported to increase the risk of HBV recurrence . Third, the results were established based on a Chinese population, and their applicability to Western populations must be separately evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Vorliegen dieser Risikofaktoren sollte man derzeit von einem Absetzen der HBIG-Therapie Abstand nehmen. Diese Empfehlungen stützen sich unter anderem auf retrospektive Analysen von 338 Patienten, bei denen sowohl eine präoperative Lamivudin-Resistenz als auch ein HCC signifikant mit einem erhöhten HBV-Rekurrenzrisiko nach Beenden der kombinierten Prophylaxe assoziiert waren [247].…”
Section: Kommentarunclassified
“…For low‐risk patients, lower HBIG doses and discontinuation of HBIG became possible provided patients continued on third generation NA long‐term (Table 2). 42‐56 The type of prophylaxis in low‐risk patients (combined short‐term HIBG + NA vs NA monotherapy with no HBIG) was extensively discussed amongst the panel. Pros and cons of both strategies are summarised in Table S2.…”
Section: Search Strategy; Selection Criteriamentioning
confidence: 99%